Caracterización de la cadena de valor del café bajo la modalidad tradicional y asociativa en el cantón Quilanga, provincia de Loja, periodo 2019-2020 - Riofrío Pogo, Daniel Alejandro (2020)
This research is intended to determine the characteristics of direct actors that are part of the coffee value chain in the canton Quilanga; and its purpose was to design the structures of value chains in both the traditional modality associative, which are made up of 6 main links and the respective actors that make up it and thus assist future research, such as a guidance document and information on the characteristics of the which own the value chains of coffee in canton Quilanga, the research is part of a group of applied studies to the main coffee cantons of zone 7 composed of Loja, El Oro and Zamora. The study has a quantitative approach complemented by qualitative tools, non-experimental methodological design of a nature descriptive, analytical, synthetic and comparative; the techniques applied were: the survey aimed at the direct actors, and the interview directed at the indirect actors of CV. In the same way his use of non-probabilistic sampling for convenience allowing us to create a sample according to the ease of access and availability of people for the application of the survey. As a result of the study it was shown that the CV under the associative modality is much more favorable, because public institutions provide greater attention in terms of the promotion of their coffee at the local and national level, and also facilitate their access to the market due to the volume of production that take hold, and the actor who has the greatest benefits is the producer because they increase their income and improve their living conditions, but the same is not true of the producer working under the traditional modality, which in this case his form of cultivation is totally different, has higher amounts of land, fewer plants per ha. And with very low coffee quintal yields and in terms of marketing it is the one that earns the least by the sale of a quintal of coffee since in this case the collector has the greatest bargaining power.